Two kinematic transformations of the Pamir salient since the Mid-Cenozoic: Constraints from multi-timescale deformation analysis - Ge, Jin; Shi, Xuhua; Chen, Hanlin; Lin, Xiubin; Ge, Weipeng; Wei, Xiaochun; Li, Feng; Chen, Jie; Li, Haibing; Cheng, Xiaogan; Zhang, Fengqi (Frontiers in Earth Science, 2022)
The Pamir salient is a key part of the Himalayan–Tibetan Plateau orogenic system and has undergone intense tectonic deformation during the India–Asian collision. Delineating the Cenozoic kinematics and geodynamics of the Pamir salient requires a comprehensive understanding of the active arcuate structures along its frontal margin, from the perspective of the multi-spatiotemporal evolution of deformation patterns. Here, we reviewed the deformation rates of the major structures at different timescales, reanalyzed the published GPS velocities, and examined the present-day seismicity to constrain the kinematics of the Pamir salient since the Late Cenozoic. Integrated with the crustal evolution history during the Middle–Late Cenozoic and the deep structure, we proposed a new model to explain the multi-stage kinematics and associated geodynamics of the Pamir salient. During ~37–24 Ma, the initial Pamir salient moved northward via radial thrusting that rotated the basins on both sides, which was driven by the continuous compression of the Indian slab after the breakoff of its oceanic part. During ~23–12 Ma, the gravitational collapse of the Central and South Pamir crusts, which was induced by the breakoff of the continental part of the Indian slab, triggered the extension within the Pamir and foreland-ward movement of the upper crust. The upper crustal materials moved in varying directions due to the differential strength of the foreland areas, transforming the crustal kinematics from radial thrusting into a combination of radial thrusting and transfer faulting. Since the coupling of the Indian and Pamir slabs at ~12–11 Ma, the deformation propagation towards the forelands accelerated, after which the kinematics of the Pamir salient exhibited asymmetric radial thrusting that has been sustained until the present. The asymmetric radial thrusting was likely driven by the compressive stress effect of the lithospheric basal shear generated by the underthrusting of the cratonic Indian lithosphere, which further led to the rollback of the Pamir slab and the consequent migratory extension in the South Pamir.